Estrategias de intervención para mitigar el impacto de Escherichia coli productor de toxina Shiga en la cadena cárnica bovina - Cap, Mariana (2021)
Shiga toxin-producing Escherichia coli (STEC) are foodborne pathogens that can cause bloody diarrhea, hemorrhagic colitis and hemolytic uremic syndrome. The meat contaminated with STEC impacts on the public health due to the risk of making the\nconsumer sick and on the economy due to the loss implied by the rejection of\ncontaminated meat destined for export. In this context, there is a strong demand to\nevaluate the effectiveness of the antimicrobial treatments available in the country against native STEC O157 and non-O157 strains. The aim of the present study was to evaluate, standardize and promote intervention strategies to reduce the presence of STEC O157 and non-O157 in beef cuts, beef trimmings (raw material for beef burger preparation)\nand ground beef. For that matter, we conducted three assays. In assay 1, we evaluated the efficacy of lactic acid (LA), peroxiacetic acid (PA), caprylic acid (CA) and electrolyzed water (EW) to reduce STEC in beef cuts. In assay 2, we evaluated the efficacy of LA,\nCA and gamma irradiation, alone and combined, to reduce STEC in beef trimmings. In assay 3, we evaluated the efficacy of gamma irradiation to reduce STEC in ground beef.\nIn the 3 assays, the effects on the sensory attributes of the most effective interventions on the different meat matrices analyzed were evaluated, and in assays 1 and 2 the effects on physicochemical parameters were also evaluated. The inoculum consisted in a cocktail of native STEC strains that belonged to the following serogroups: O26, O103, O111, O145 and O157. Samples were inoculated with two bacterial concentrations, high\nand low. Samples with high inoculum (HI) were analyzed by plate count while samples\nwith low inoculum (LI) were analyzed by real-time PCR after an enrichment step.\nEffectiveness was estimated in terms of log reductions for samples with HI and in terms of reduction of the percentages of positive samples for stx and eae genes in samples with LI. Results from assay 1 demonstrated that from the four interventions evaluated,\nonly CA was effective to reduce STEC. The achieved reductions were 0.8 log CFU/g in samples with HI and 77% in samples with LI. Results from assay 2 demonstrated that the most effective treatment to reduce STEC was 2 kGy of gamma irradiation as the\nreduction was higher than 5 log CFU/g in samples with HI and of 100% in samples with LI. The combined treatment of LA and gamma irradiation increased STEC lethality in\nsamples with HI but not in samples with LI. Results from assay 3, demonstrated that 1 kGy was enough to reduce 5 log CFU/g in ground beef samples with HI. However, when samples with LI were subjected to that dose it did not achieve a total STEC inactivation.\nThe results of the present study demonstrate the importance of assessing antimicrobial treatments with more than one level of inoculum. Furthermore, increase the knowledge about different strategies to reduce STEC contamination in beef products without\nsignificantly affecting nor physicochemical characteristics neither sensory attributes